Архітектурна майоліка львівської сецесії. Аналіз типології, стилістики та композиції на базі натурних досліджень - Казанцева, Т. (Студії мистецтвознавчі, 2009)
Natural investigations on L’viv buildings in the «Secession» style have been found out 63 facades decorated by majolica. Not monolith ceramic historic elements (as in the «picturesque» style) but square tiles had became the dominate majolica decoration. Dark blue, violet, purple and blue colors were used more often, green, orange and yellow – more rarely. As a rule the surface of the «Secession» tiles is smooth and sometimes is covered by luster. The decorative ceramic rivets as a truncated gold pyramid from time to time have been placed in the tiles joints in one- and two-colored compositions. Unlike the «picturesque » style the «Secession» tiles never were located as a rhombus. The single tiles were used to decorate architectural elements or to form compositions which stylize friezes, window frames, pilasters etc. The tiles location on the various forms of planes which were placed round the windows or facades attics has been obtained the great widening. The new method was entire facing with tiles of the façade’s part (attic or upper stories).